CENTRAL ASIA AND THE CAUCASUS: POST-CRISIS ANALYSIS OF THE STATE AND SOCIETY - ERGASHEV, Bakhodyr (CENTRAL ASIA AND THE CAUCASUS, 2009)
On the whole, little or no attention is paid to the forecasts of post-crisis development in Central Asia and the Caucasus that are scattered among the publications on the post-crisis world. Indeed, so far these regions essentially remain outside the global industrial market, while the raw-material orientation of their economies allowed practically all eight of them to avoid serious socioeconomic upheavals. It is impossible, however, to supply an exhaustive forecast of the crisis’s economic, political, cultural, demographic, and other impacts. Kazakhstan was the first among the Central Asian (and the post-Soviet countries in general) to face the crisis. This happened in the fall of 2007 when the oil reserve fund was opened, and the state tried to stifle the crisis by urgently pumping state money into the republic’s economy. This means that the numerous official statements, expert assessments, and constructive suggestions coming from the Kazakhstan opposition should be regarded as belonging to the so-called inertia model of social and economic development promoted in the republic for many years. The international conference held in Bishkek in March 2009 and the International Conference on the Social Impact of the Economic Crisis in Eastern Europe, Central Asia and Turkey held in December 2009 in Almaty pointed out that the countries for which “Russia remains a main trading partner and a major source of remittances” suffered more than many of the others.1